2011
DOI: 10.1111/j.1475-682x.2010.00360.x
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Customer Racial Discrimination in the Secondary Baseball Card Market*

Abstract: A growing body of literature in a variety of disciplines has appeared over the last 20 years examining customer racial bias in the secondary sports card market; however, consensus on the matter has yet to emerge. In this article, we explore the more subtle ways that a player's race/ethnicity may affect the value of his sports card including a player's skin tone (light- to dark-skinned). Data were obtained for 383 black, Latino, and white baseball players who had received at least one vote for induction into Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…For instance, Nardinelli and Simon [35] suggest that the race of the player printed on the baseball cards can affect the consumer's desired price. On the other hand, other studies have reported no or insignificant evidence of racial discrimination among consumers in the case of the baseball card market [31,43]. However, to date, whether ethics-related endogenous predictors such as gender and skin tones affect NFT valuation remains unknown.…”
Section: Background and Related Work 21 Nfts Marketplaces And Ethicsmentioning
confidence: 94%
See 1 more Smart Citation
“…For instance, Nardinelli and Simon [35] suggest that the race of the player printed on the baseball cards can affect the consumer's desired price. On the other hand, other studies have reported no or insignificant evidence of racial discrimination among consumers in the case of the baseball card market [31,43]. However, to date, whether ethics-related endogenous predictors such as gender and skin tones affect NFT valuation remains unknown.…”
Section: Background and Related Work 21 Nfts Marketplaces And Ethicsmentioning
confidence: 94%
“…While studies on discrimination in NFT transactions are largely scant, prior work on racial discrimination in physical collectibles suggests multiple sources of racial discrimination in prices, including suppliers, customers, and other parties [6]. For customer racial discrimination, studies that have examined gender and racial influences on prices have mixed, and contradictory findings [31,35,36,43]. For instance, Nardinelli and Simon [35] suggest that the race of the player printed on the baseball cards can affect the consumer's desired price.…”
Section: Background and Related Work 21 Nfts Marketplaces And Ethicsmentioning
confidence: 99%
“…ESPN uses a standard face-shot for the photo on every player’s individual page on ESPN.com. We followed the technique used most commonly in the literature (Berri et al , 2014; DeWerff, 2016; Primm et al , 2011; Robst et al , 2011) and applied Adobe Photoshop to take a sample from the direct center of each player’s forehead and then measure the level of RGB saturation. Photoshop then provides a score ranging from 000 (completely black) to 999 (completely white).…”
Section: Methodsmentioning
confidence: 99%
“…Research has covered discrimination in hiring, in retaining (along seasons), in segregating (to specific game roles), and in salary of players, as well as customer discrimination. The last topic is also known as fan discrimination, typically measured using TV audience (Aldrich et al, 2005), game attendance (Foley & Smith, 2007;Hersch, 2009;Wilson & Ying, 2003), the trading value of sport cards (Broyles & Keen, 2010;Primm et al, 2011), the votes for best player awards (Jewell et al, 2002). As far as salary discrimination in professional sports is concerned with, there is an extensive literature on the subject.…”
Section: Labour Economic Perspectivementioning
confidence: 99%